Unlocking the Satisfaction: Discover the Drivers of Customer Satisfaction on TAOBAO - Ng, Wei Chien; Yusof, Rosmelisa; Mazlan, Nurul Annisa Binti; Oh, Kai Xin; Ong, Jin Wei; Ong, Sin Yee; Kee, Daisy Mui Hung (The Global Academia Publisher, 2025)
This study examines the interrelationships between customer satisfaction and perceived benefits of the Taobao online shopping platform among Malaysian users. A quantitative research approach was employed by distributing a structured questionnaire to 150 Taobao users in Malaysia through Google Forms. Regression analysis was used to assess the influence of perceived ease of use, perceived trust, perceived convenience, and perceived usefulness on customer satisfaction. The findings indicate that all four factors positively and significantly influence customer satisfaction, with perceived ease of use emerging as the most dominant predictor (β = 0.284), followed by perceived trust (β = 0.258), perceived convenience (β = 0.255), and perceived usefulness (β = 0.180). The regression model explains 77.1% of the variance in customer satisfaction (R² = 0.771), demonstrating strong explanatory power. These results suggest that usability, security, operational efficiency, and functional value collectively shape customer satisfaction in a cross-border e-commerce context. This study contributes to the e-commerce literature by identifying the relative importance of key satisfaction drivers and provides practical insights for platform developers and marketers to enhance user experience, build trust, and sustain competitiveness in the rapidly growing online retail environment.